Lives of the great gardeners - Anderton, Stephen (London : Thames & Hudson Ltd., 2017)
Throughout history great gardeners have risen from all walks of life. What they all have in common is the ability to take an idea and develop it in a new manner relevant to their times. The book is divided into several sections. 'Gardens of Ideas' moves from the politically allusive gardens of 18th-century England made by men such as William Kent, to Charles Jencks' Scottish garden inspired by 21st-century cosmography. 'Gardens of Straight Lines' explores the lives of the great formalist gardeners, from Le Notre at Versailles to the rational English minimalism of contemporary designer Christopher Bradley-Hole. 'Gardens of Curves' begins with that great exponent of the English landscape garden, 'Capability' Brown, and leads to the extraordinary Brazilian designer Roberto Burle Marx. Finally, 'Gardens of Plantsmanship' moves from the father of naturalistic planting, William Robinson, to the sweeping prairies of New York's favourite Dutch designer, Piet Oudolf. With an outstanding text by the award-winning gardens writer Stephen Anderton, this book will appeal to garden lovers everywhere.
boek